Esthetic Composition of Smile in Individuals with Cleft Lip, Alveolus, and Palate: Visibility of the Periodontium and the Esthetics of Smile. (21st November 2012) - Esper, Luis Augusto; Sbrana, Michyele Cristhiane; Cunha, Mércia Jussara da Silva; Moreira, Guilherme Santos; de Almeida, Ana Lúcia Pompéia Fraga
Abstract : Objective . To evaluate characteristics of smile related to visibility in individuals with cleft lip, alveolus, and palate. Design . Cross-sectional. Setting . HRAC/USP, Brazil. Patients . Individuals with repaired complete unilateral cleft lip and palate( n = 45 ), aged 15–30 years. Interventions . Frontal facial photographs were obtained in natural and forced smiles( n = 135 ) . Six specialists in periodontics evaluated the photographs as to the smile line, thickness, and curve of the upper lip. Main Outcome Measures . The cleft area was compared with the contralateral region. Results were expressed as percentages and means. The findings were compared between groups of periodontists. Results . Statistically significant relationship was observed in the smile line between examiners and between natural and forced smiles, regardless of the association with the cleft side. The lip was thicker at rest and thinner in the forced smile, as also evaluated by the group not experienced with cleft care. The curve of the upper lip in natural and forced smiles was considered as close to straight by both groups, regardless of the cleft. Conclusion . The smile in individuals with clefts was regarded as average for both cleft and noncleft sides. The thickness was characterized as average to thin, being thinner in forced smile and when analyzed by the group not experienced with cleft care. In the average, the curve of the upper lip was considered as straight. The present study elucidates some characteristics related to the smile in individuals with repaired unilateral cleft lip, alveolus, and palate.